2014
DOI: 10.1038/hdy.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic evidence for two mesic refugia in a biodiversity hotspot

Abstract: Phylogeographic studies of flora in species-rich south-western Australia point to complex evolutionary histories, reflecting patterns of persistence and resilience to climatic changes during the Pleistocene. We asked whether coastal areas of the mid-west and south, as well as granite outcrops and inland ranges, have acted as major refugia within this region during Pleistocene climatic fluctuations by analysing phylogeographic patterns in the shrub Calothamnus quadrifidus R.Br. (Myrtaceae). We determined variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
6
33
0
Order By: Relevance
“…More northern occurring species, such as P. nelshoogteensis and P. fasciatipennis , appeared to have persisted in northern refugia (Figs S5 and S17). Such potential long‐term refugia (Ibrahim et al ., ; Nistelberger et al ., ) of Pleophylla in the northern parts of the Great Escarpment were also supported by the high haplotype diversity that was recovered for the northern species in this study (Figs e, g and e, g) as well as the occurrence of locally endemic species (e.g., P. warnockae , P. pseudopilosa , P. ruthae ; Eberle et al ., ).…”
Section: Discussionsupporting
confidence: 81%
“…More northern occurring species, such as P. nelshoogteensis and P. fasciatipennis , appeared to have persisted in northern refugia (Figs S5 and S17). Such potential long‐term refugia (Ibrahim et al ., ; Nistelberger et al ., ) of Pleophylla in the northern parts of the Great Escarpment were also supported by the high haplotype diversity that was recovered for the northern species in this study (Figs e, g and e, g) as well as the occurrence of locally endemic species (e.g., P. warnockae , P. pseudopilosa , P. ruthae ; Eberle et al ., ).…”
Section: Discussionsupporting
confidence: 81%
“…Dated phylogeographies are available for species in at least five families of plants (see Table 1), and many studies on widespread species have identified divergent lineages that separated during the mid-Pleistocene, e.g. Eucalyptus loxophleba (Byrne & Hines, 2004), Acacia acuminata (Byrne et al, 2002), Santalum spicatum (Byrne, Macdonald & Brand, 2003) and Calothamnus quadrifidus (Nistelberger et al, 2014). Older intraspecific divergences in the late Pliocene have also been noted in the widespread E. marginata (Wheeler & Byrne, 2006) and the restricted and disjunct Lambertia orbifolia (Byrne, Macdonald & Coates, 1999).…”
Section: (5) Plant Datamentioning
confidence: 99%
“…Parallel divergences between northern and southern clades of other species in the Western Australian Floristic Region have been shown in plant and animal biogeographic studies, and may be driven by climatic change from the early to late Pleistocene (Byrne & al., , ; Fujioka & al., ; Murphy & al., ; Nistelberger & al., ). The microsatellite data show the greatest difference between the southern populations (group IV) and all other accessions (Fig.…”
Section: Discussionmentioning
confidence: 97%